Pilot Study of Intraperitoneal Administration of Triamcinolone Acetonide for Cancerous Ascites in Patients With End-Stage Gynecological Cancer - Shoji, Tadahiro; Takatori, Eriko; Miura, Yuki; Takada, Anna; Omi, Hideo; Kagabu, Masahiro; Honda, Tatsuya; Miura, Fumiharu; Takeuchi, Satoshi; Sugiyama, Toru (International journal of gynecological cancer, 2014)
OBJECTIVEPatients with end-stage cancer have poorly controlled ascites retention resulting due to cancerous peritonitis. We intraperitoneally administered triamcinolone acetonide (TA) to patients with end-stage gynecological cancer as a pilot study, and our treatment results are reported herein. PATIENTS AND METHODSWe enrolled 26 patients with end-stage gynecological cancer requiring frequent abdominal paracentesis for ascites drainage between April 2010 and September 2012. The volume of ascites drainage was 2000 to 3000 mL per drainage session, and TA at 10 mg/kg was intraperitoneally administered after drainage. We compared abdominal paracentesis intervals, performance status (PS), total protein level, albumin level, white blood cell count, changes in C-reactive protein (CRP) level, and adverse events before and after TA use. RESULTSTriamcinolone acetonide was administered to 26 patients for a total of 59 times. The abdominal paracentesis intervals, PS, and mean (SD) of C-reactive protein before and after TA use were 13.2 (12.6) days and 21.9 (23.6) days (P = 0.0117), 2.4 (0.7) and 1.6 (1.1) (P < 0.0001), and 7.5 (5.2) mg/dL and 5.5 (5.0) mg/dL (P = 0.007), respectively. With regard to adverse events, abdominal pain of grade 2 was observed once (1.7%), but there were no other acute adverse events. Four subjects (15.4%) had intestinal perforation. CONCLUSIONSIntraperitoneal administration of TA after drainage was considered to be a useful treatment, as it seems to extend paracentesis intervals and improve PS while maintaining quality of life for end-stage gynecological cancer patients with massive ascites.